1983
DOI: 10.4141/cjss83-009
|View full text |Cite
|
Sign up to set email alerts
|

VESICULAR ARBUSCULAR MYCORRHIZAL SPORE POPULATIONS IN VARIOUS SASKATCHEWAN SOILS AND THE EFFECT OF INOCULATION WITH Glomus mosseae ON FABA BEAN GROWTH IN GREENHOUSE AND FIELD TRIALS

Abstract: L'inoculation intensifie 6galement la colonisation radiculaire et augmente l'absorption totale de phosphore.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

1994
1994
2003
2003

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 12 publications
1
17
1
1
Order By: Relevance
“…Mean percent colonization was signi®cantly greater in sweet corn grown in subsoils previously cropped to wheat (52%) than fallowed (40%) at the 0.001 level. This observation supports other research reporting that fallowing leads to declines in AM colonization (28,29,30,31,33). However, none of these reports involved subsoils as the growth medium nor measured colonization over the growing season.…”
Section: Mycorrhizal Colonizationsupporting
confidence: 73%
See 1 more Smart Citation
“…Mean percent colonization was signi®cantly greater in sweet corn grown in subsoils previously cropped to wheat (52%) than fallowed (40%) at the 0.001 level. This observation supports other research reporting that fallowing leads to declines in AM colonization (28,29,30,31,33). However, none of these reports involved subsoils as the growth medium nor measured colonization over the growing season.…”
Section: Mycorrhizal Colonizationsupporting
confidence: 73%
“…Fallowing reportedly leads to declines in AM colonization and to plant nutrient de®ciencies (28,29,30,31,32,33). Kabir et al (34) found that AM ef®ciency and plant content of P and Zn decreased with increasing length of fallow.…”
Section: Fallowing Versus Cropping and Mycorrhizal Colonizationmentioning
confidence: 99%
“…The lowest spore densities were found in samples taken from fallow soils (Table 4). Other researchers found that AMF colonization and AMF spores density declined as a result of fallow (Black & Tinker, 1979;Kucey & Paul, 1983). Fallow was reported to decrease the organic matter content and microbial activities in general (Black & Tinker, 1979).…”
Section: Resultsmentioning
confidence: 99%
“…Canadian surveys for mycorrhizal fungi diversity have been done on different ecosystems and habitats such as orchard fields (Dalpé et al1986;Traquair and Berch 1988), maple forests (Moutoglis and Widden 1996;Coughlan et al 2000), coniferous (Egger and Paden 1986;Hutchinson 1992;Bradbury et al 1998;Kernaghan and Currah 1998;Durall et al 1999;Kranabetter et al 1999) and deciduous Laurentian forests (Villeneuve et al 1989), sand dunes (Dalpé 1989;Dalpé and Mitrow 1993;Little and Maun 1996), urban conifer trees (Danielson and Pruden 1989), peat land (Hambleton et al 1999), and old acid meadows (Hamel et al 1994(Hamel et al , 1996. Fungal diversity was investigated in several indigenous and cultivated plants such as alfalfa (Kucey and Diab 1984), barley Tewari 1986, 1993), beans (Kucey and Paul 1983;Kucey et al 1985), Cistaceae (Malloch and Thorn 1985), Ericaceae (Hambleton and Currah 1997; Berch et al 2001) such as blueberry (Couture et al 1983) and salal (Xiao and Berch 1992, Epacridaceae (McLean et al 1999) lentils (Talukdar and Germida 1993), orchids (Currah et al 1988(Currah et al , 1990, lodgepole pine (Bradbury 1998;Bradbury et al 1998), strawberry (Muamba et al 2002), wheat (CadeMenun et al 1991;Takukdar and Germida 1993) 1990; Kohn and Stasovski 1990;Gardes and Dahlberg 1996) and alpine tundra (Stoyke and Currah 1991), the boreal forest …”
Section: Fungal Diversity and Plant Mycorrhizal Statusmentioning
confidence: 99%